Association of migration and family planning use among women in Malawi: Evidence from 2019/2020 Malawi Multiple Indicators Survey - Reuben Christopher Moyo; Dumisani Nkhoma (BMC, 2023)
Abstract Background Family planning (FP) is known to bring multiple benefits to people both individually and collectively. Individually, FP has been associated with reduction in risk of unintended pregnancy which also correlates with low child mortality rates. Child mortality rates in women with child spacing of less than two years are 45% higher compared to their counterparts with child spacing of more than two years. Several factors that predict FP utilisation among women of childbearing age have been identified but there is limited literature on how migration impacts FP utilisation in Malawi. Our current study aimed at assessing the association between migration and modern contraceptive use among women of childbearing age in Malawi. Methods Data for this study came from a nationally representative 2019/20 Malawi multiple cluster indicator survey (MICS). At total of 24,543 women aged 15 to 49 participated in the survey. Contraceptive prevalence rate (CPR) analyses were conducted separately on all women of childbearing age and married women. The data was analysed using the complex survey data approach by applying sampling weights to correct unequal representation of participants at cluster, district, and regional level. We used binary logistic regression to assess association between migration status and modern contraceptive use among all women of childbearing age and married women separately. We included age, age at first sex, age at marriage, region of residence, education, residence wealth index and presence of disability as confounders in our final multivariable models. Results The overall CPRs for married women and for all women of childbearing age were 64.7% and 40.5% respectively. The CPRs for all women of childbearing age were 40.5% for non-migrants and 33.0% for migrant women. For married women, CPRs were 51.5% for migrant women and 65.5% for non-migrant women. The fully adjusted odds ratios for the association between migration status and modern contraceptive use were 0.62 (0.49-0.78) for married women and 0.65 (0.52-0.80) for all women of childbearing age. Conclusions We conclude from our findings that migrant women were significantly less likely to utilize modern contraceptive methods for both married women and all women of childbearing age. Deliberate efforts are required to ensure that migrant women of childbearing age have equal access to sexual and reproductive health services which includes family planning.